The Tissue‐Supported Sling Suture: Technique and Clinical Applications. Issue 3 (19th November 2019) - McGary, Ryan T.; Johnson, Thomas M.; Berridge, Joshua P.; Wilson, James P.; Baron, Dmitry
Abstract : Introduction: Continuous and interrupted sling sutures (ISSs) are used around teeth in contemporary periodontics. However, conventional ISSs depend upon favorable tooth morphology for stability through the early healing period. The purpose of this report is to present a variation of the classic ISS that does not rely on favorable tooth morphology. Case Series: Tissue‐supported sling sutures (TSSs) were used for six patients undergoing root coverage, gingival augmentation, or pontic site development (guided bone regeneration) procedures. Conclusions: Although techniques such as vertical mattress suturing may support greater coronal flap advancement, the TSS technique does maintain coronal flap position while minimizing trauma to papillae. TSS stability is independent of tooth morphology and may offer clinicians flexibility in achieving reliable closure over hard and soft tissue implants. Like mattress sutures, TSSs reduce tension at the crestal incision line in tissue grafting procedures.